Review of Transport and Obligations of Vehicles in Kalabahi – Kupang Tracking, East Nusa Tenggara - Hendri Ginting; Noor Sulistiyono; Tri Meyla Damayanti (IWJ : Inland Waterways Journal, 2019)
Kalabahi ferry port is one of the ferry ports located in Alor district as a transport node is used by locals and tourists. Kalabahi Ferry Port managed directly by the Regional Land Transport Hall business XIII East Nusa Tenggara province. In the security and safety of the transportation system highly favored as a form of good service delivery. Safety was shown not only to the service user, but also to the vehicle operator and the operator of the ship. As well as setting the transport and cargo handling vehicles on board, the better arrangement and handling of vehicles on board the better the level of security and safety of vehicles on board and vice versa. Settings transport and cargo handling vehicles on the boat is good for the service user / owner of the vehicle, as well as security and safety for vehicles on board and are not harmful to the operator of the vessel that can be done by means of an approach based on the arrangement of the transport vehicle, putting distance between vehicles safe and mounting strap on the vehicle (lashing) contained in the regulation number 115 of 2016 on procedures for the transport of vehicles on board and regulation Number 30 of 2016 concerning the binding obligation on ships crossing transport vehicles.